MARKETING ACTIVITY OF ENTERPRISES IN A CRISIS - BUBENETS, Iryna; CHATCHENKO, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The global crisis created by the pandemic in 2019 and Russia's military attack on Ukraine on February 24, 2022 created harsh conditions for business to operate. Entrepreneurs need to be ready to respond in a prompt way to the needs and behavior of consumers to continue their business. The marketing activities of enterprises are currently an extremely important problem in the martial law of the country, as the previous crisis associated with COVID-19 has already made some adjustments in the work of enterprises and society.The article studied the specifics of enterprises’ marketing activities in the crisis caused by COVID-19 and the martial law in Ukraine. It is indicated that entrepreneurs have reduced their marketing costs and use marketing methods that focus on promoting goods or services over the Internet, developing online retail skills. The essence and difference of e-commerce from traditional are considered. Given the work experience in the crisis caused by COVID-19, companies consider social networks and their opportunities for the development of their business as a very promising component of successful marketing activities. The dynamics of Internet users’ growth and online sales in Ukraine in recent years are analyzed. It is noted that social networks are one of the most effective tools of marketing communications, which does not require significant costs and has a large audience of users. Thus, companies are advised to establish around this tool their marketing strategy for social media marketing (SMM). The advantages and tasks of SMM are defined. To use the POST-method in the development of SMM strategy is proposed (P: People - analysis of the target audience, O: Objectives - definition of clear goals, S: Strategy - development and growth of consumer interaction strategy, T: Technology - selection of social media tools).Thus, it should be noted that the crisis in Ukraine leads to the requirement to create budgetary and effective communication channels. One of such channels is social networks, and an effective tool of marketing communications is social media marketing (SMM). An important advantage of such a tool is that it is almost free, has a large audience of users, various means of influence on the target audience, as well as the strategy (SMM) is a logical continuation of the functional marketing strategies.Prospects for further research in this field may be the issues of assessment of marketing activities effectiveness in social networks in a crisis.
Keywords: marketing activities; social media marketing; e-commerce; social networks; marketing strategy; communication channel; crisis